Educação ambiental: concepções e práticas pedagógicas de professores da rede pública municipal de Simão Dias/SE - Santos, Fernanda Ramos (2013)
In confronting the current environmental crisis, understood by many as a civilizational crisis, which, more than just ecological also plays a social character, Environmental Education comes with a commitment to promote changes in values, behaviors and attitudes to build a society that more just and environmentally sustainable. Thus, recognizing the different possible contexts for the realization of Environmental Education, this study sought to search within the school context the concepts and pedagogical practices in Environmental Education teachers of municipal public Simão Dias. For this analysis were investigated: profile of the teacher and his training in Environmental Education, teaching practice, conceptions about the environment and Environmental Education, as well as the performance of the COM-VIDAs (Commission on Environment and Quality of Life in School). This being characterized as a search for qualitative and quantitative nature, questionnaires and semi-structured interviews were used as methodological resources. In a universe of 89 teachers from different subject areas, which act in the final grades of Elementary School (6th to 9th grade), 54 voluntarily participated in the study by answering the questionnaire. These teachers, six also expressed interest in participating in structured interviews. As the concepts of environment, most teachers perceive the environment only in their natural aspects (naturalistic view) or just as a resource for human survival (anthropocentric), which suggest practices in environmental education geared solely to preservation and conservation of natural resources. Teachers also recognize various environmental problems of the school community, however, there are few actions performed in schools, through the agency of COM-VIDAs, in view to discuss and propose solutions to the environmental issues local community. Thus, we recognize the need to strengthen the work of COM-VIDAs to ensure the permanent, critical and transformative character of Environmental Education. Therefore, it is important that the county promotes, through the City Department of Education, the continuity of municipal meetings in Environmental Education, as well as establish partnerships with higher education institutions to offer continuing education courses for teachers in perspective to offer theoretical and methodological subsidies for inclusion of Environmental Education in the school context.